The use of children as a tactic of intimate partner violence and its relationship to survivors' mental health - Clements, Kathryn A. V. (Journal of family violence, 2022)
Although prior research has established that intimate partner violence (IPV) often leads to increased depression, anxiety and post-traumatic stress disorder (PTSD), little is known about how often abusive partners and ex-partners use survivors’ children as an abuse tactic, nor whether this form of IPV also is detrimental to survivors’ mental health. The current study interviewed 299 unstably housed survivors of intimate partner violence shortly after they sought services from a domestic violence agency. All participants were parents of minor children. In-person interviews asked about abuse experienced in the prior six months, including the ways children were used as a form of IPV. Participants were also asked about their current depression, anxiety, and symptoms of PTSD. As hypothesized, the majority of parents reported their abusive partners and ex-partners had used their children as a form of IPV to control and hurt them. Further, after controlling for other forms of IPV, use of the children significantly predicted both increased anxiety and greater number of PTSD symptoms. Results show the importance of focusing on the use of children as a common and injurious form of abuse used against survivors of intimate partner violence (IPV).